Pengaruh Penerapan Model Pembelajaran Berbasis Proyek terhadap Keterampilan Membaca dan Menulis Siswa pada Jenjang Pendidikan Dasar - Siti Khotijah; Nurmalina Nurmalina; Ramdhan Witarsa (Universitas Negeri Makassar, 2023)
Project-based learning model is a learning model that involves students in designing, creating, and displaying products to improve a certain skill based on real-world needs. This research aims to measure how much influence the project-based learning model has on students' reading and writing skills at the primary education level. The method used in this research is a quasi-experimental method. The research instrument used was an observation sheet for students' reading and writing skills. The results of the research show that the project-based learning model has a significant effect on students' reading and writing skills at the primary education level. Students' reading and writing skills show that students' basic literacy in terms of reading and writing is already in the very skilled category. The project-based learning model can be applied to research other basic literacy that is still needed by students at the primary education level. Teachers should be more creative and innovative in teaching other basic literacys so that students' competencies can compete globally.